The Influence of Hedonic Shopping Motivation, Product Knowledge, and E-Wom on Impulsive Purchase of Eiger Products in the Shopee Marketplace - Pratama, Muhammad Rifqi; Nuvriasari, Audita (East Asian Journal of Multidisciplinary Research, 2024)
The current development of the internet is not only a medium for information and communication, but the internet can fulfill people's desires for practical shopping, namely online shopping. One of the developments of the internet in shopping is the emergence of e-commerce. However, with the emergence of e-commerce, we still have to be wary of the emergence of impulse buying, which is a condition that occurs when individuals experience a sudden feeling of urgency that cannot be resisted. Several factors cause the emergence of impulse buying, including; (1) Hedonic Shopping Motivation; (2) Product Knowledge; and (3) Electronic Word of Mouth (E-WoM). So this research aims to find out how Hedonic Shopping Motivation, Product Knowledge, and (E-WoM) influence partial impulse buying of Eiger products in the Shopee marketplace. This research uses a quantitative research method, with a purposive sampling technique to produce 100 respondents. The data analysis was carried out using multiple linear regression, which then analyzed the hypothesis based on the t-test. The results obtained are that Hedonic Shopping Motivation has a positive and significant effect on Impulse Buying, Product Knowledge has a positive.